DETERMINANTS OF ACCOUNTING APPLICATION ADOPTION IN VILLAGE OWNED ENTERPRISE: AN INTEGRATED TAM-TOE PERSPECTIVE - Widianingsih, Rini; Sunarmo, Agus; Suparlinah, Irianing; Sugiarto, Sugiarto (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study investigates the determinants of accounting application adoption in Village Owned Enterprises (BUMDes) by integrating the Technology Acceptance Model (TAM) and the Technology–Organization–Environment (TOE) framework. The digitalization of financial management in BUMDes is essential to enhance transparency and accountability; however, technology adoption remains uneven. Using a quantitative survey approach, data were collected from 50 BUMDes in Banyumas Regency that have implemented accounting applications for at least six months. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that perceived usefulness and perceived ease of use significantly influence behavioral intention. Furthermore, technological readiness, organizational support, and environmental pressure significantly affect behavioral intention, which in turn positively influences actual system use. This study contributes to the accounting information systems literature by demonstrating that the integration of TAM and TOE provides a comprehensive explanation of technology adoption behavior in village-level public enterprises. The results offer practical implications for policymakers and BUMDes managers in accelerating digital financial governance.